Autonomy, Empathy and Transformation in Language Teacher Education: A Qualitative Study - Larissa Borges; Eduardo Castro (Studies in Self-Access Learning Journal)
The complexity of language teaching and learning requires teachers to be able to reflect on their own practices, adapt to different situations, and seek solutions that may meet the needs and interests of their students (Borges, 2019; Borges & Magno e Silva, 2019). Moreover, teachers ought to make their learners’ experiences more meaningful and personal in the classroom. In regard to this, teacher education should involve reflections on empathy, so that pre-service teachers can develop the ability to listen actively, welcome their students’ perspectives, and put themselves in their shoes (Mercer, 2016). Teacher education should also entail reflection on autonomy, in a way that pre-service teachers can exercise their agency in their own education, as well as create conditions for the development of autonomy in their classrooms. With that in mind, this study aims to investigate pre-service language teachers’ transformation during two teaching methodology courses at a university in Northern Brazil. Data were generated through teaching diaries and in-class reflections, which were then analyzed qualitatively (Saldaña, 2021). The findings indicate that pre-service teachers not only became aware of the importance of encouraging their learners’ autonomy, but they also became aware of learning autonomously themselves. The diaries also revealed how considering empathy in their practices was pivotal to fostering learner autonomy in the classroom. Implications for language teacher education are discussed.